Lymphoid blastic crisis in Philadelphia chromosome-positive chronic granulocytic leukemia following high-grade non-Hodgkin's lymphoma A case report and review of literature - L Mele; L Pagano; F Equitani; P Chiusolo; E Rossi; G Zini; L Teofili; G Leone (Haematologica, 2000)
In this paper we describe a case of a 65-year old man with a lymphoid blastic crisis of a chronic granulocytic leukemia occurring seven years after a palatine tonsillar non-Hodgkin's lymphoma treated with chemotherapy and radiation therapy. Bone marrow cytogenetic study demonstrated the presence of the typical t(9;22)(q34;q11) and the molecular biology study showed the p210 rearrangement (b2a2). The patient died within a few months, unresponsive to any treatment. This is the first case, described in literature, of a secondary chronic granulocytic leukemia onset with a lymphoid blastic crisis. The authors report the case and a literature review.